Elastic and thermodynamic properties of Fe3Ga from first-principles calculations. (March 2016) - Lin, Ya-Ning; Li, Lin-Ling; Yan, Xiang-Hong; Zhang, Ya-Ping; Zhang, Dong-yun; Zhang, Peng
Abstract: First-principles calculations within the framework of density functional theory (DFT) are performed to investigate the elastic and thermodynamic properties of DO3 -type Fe3 Ga alloy. The obtained lattice constants and the bulk modulus are in good agreement with available experimental data. In terms of the calculated formation energy and Poisson's ratio, the Fe3 Ga alloy is mechanically stable and exhibit a negative Poisson's ratio of −0.81 along the 〈110〉 direction. The thermodynamic properties such as the Gibbs free energy, thermal expansion, and the specific heat are obtained by the first-principles phonon calculations with the quasiharmonic approximation method. The predicted coefficient of linear thermal expansion and specific heat may provide a helpful reference for experimental work. Highlights: Elastic and thermodynamic properties of Fe3Ga are calculated by first principles. Phonon dispersions of Fe3Ga under different temperature are obtained. The thermal expansion coefficient and the heat capacity at constant pressure are predicted.